Development of Interactive Worksheets with Artificial Intelligence for Students Based on Bojonegoro Local Wisdom Towards Literacy Skills of Madrasah Ibtidaiyah Students - Suttrisno, Suttrisno; Yulia, Nurul Mahruzah; Ibrahim, Baffa Bashari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
This study aims to develop interactive student worksheets (LKPD) based on Artificial Intelligence (AI) that integrate Bojonegoro's local wisdom to improve literacy skills among Madrasah Ibtidaiyah (MI) students. These worksheets are designed to utilize AI technology in delivering engaging and contextual learning materials that reflect cultural values and local wisdom. The research employed a Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Results showed a 94% validation score, classifying the AI-based interactive LKPD as excellent and ready for use without revision. The worksheets effectively enhanced students’ literacy—especially in understanding and appreciating local content—demonstrated by an N-Gain score of 0.7–0.8 (high category). The classical learning mastery rate reached 93–95%, indicating that the majority of students achieved the set competency standards. Both teachers and students responded positively to the interactive and user-friendly design. Consequently, the AI-based LKPD presents a viable alternative as an innovative learning medium that supports literacy development while preserving Bojonegoro’s cultural heritage.